Caso de estudio: ioi’s global challenge: moving up the palm oil value chain - Reinoso Valdivieso, Paula (2019)
Palm oil is a highly competitive and continuously growing industry that has several established companies, among them is the IOI group “Industrial Oxygen Incorporated” of Malaysia, this is a multinational family business dedicated to the oil industry of Palma with three business units: oleochemicals, refinery and special oils and fats "Loders Croklaan", which had a rapid expansion between Europe, Asia and North America from the 1980s to the present day. However, in the period from 2013 to 2017, it suffered an economic crisis that led to the rethinking of the business strategy as a whole and to a greater focus on the area of development of special oils and fats. The 2025 Plan proposed by Julian Veitch, manager of "Loders Croklaan", is focused on the development and research not only of new products but also new markets in order to expand geographically and expand its product catalog. both products and markets. This ambitious strategy generates distrust of the CEO of the IOI Group. The research carried out concludes that the 2025 Plan is a strategy that will give the desired results if, at the same time, strategic alliances are used to enter new markets, since the company has cost production processes, as well as focusing on research and development. of new products, the degree of indebtedness is higher, so this strategy is the cheapest. Likewise, internal communication must improve significantly due to being the cause of serious errors in the past, such as with environmental certificates. Improving communication not only helps in your internal processes but also in your international marketing and the image that you pose to your clients.